The effect of emergency obstetric and newborn care training interventions on knowledge and skills of midwifery students prior to graduation in Kenya: A quasi-experimental study using a non-randomised controlled study design - Duncan N. Shikuku; Fiona Dickinson; Helen Allott; Sarah White; Sarah Bar-Zeev; Charles Ameh (Elsevier, 2024)
Introduction: Improving access to emergency obstetric and newborn care (EmONC) improves maternal and newborn health. However, there is evidence that the pre-service midwifery training curriculum is deficient in developing countries. Purpose: This study measured the effectiveness of pre-service Emergency obstetric care training intervention package on the knowledge and skills of final year midwifery students in Kenya. Methods: The study was a quasi-experimental controlled trial (ISRCTN 74563398) with one control and two intervention arms (full and partial), involving 12 Kenya Medical Training Colleges (KMTCs) and 381 final year midwifery students. Intervention arms' KMTCs received EmONC skills training equipment, training of lecturers on teaching methods, EmONC and clinical supervision skills, (and 12 months of mentoring for full intervention arm). Control arm KMTCs had no intervention. Students' knowledge and practical skills scores 12 months after the bundle of interventions were analysed using mixed effects linear models. Results: A statistically significant difference was detected between the study arms for the practical skills test (p < 0.001) but not for the knowledge test (p = 0.23). The odds of achieving scores of 80 % or higher in the knowledge test was significantly higher in the full intervention group A compared to the control group OR 3.2 (1.1 - 9.8), p < 0.05. The scores in the skills tests were significantly higher in the intervention groups A and B compared to the control group 14.5 (4.2 - 24.9), p < 0.001 and 24.9 (14.5-35.2) respectively. Conclusion: The pre-service EmONC intervention package was effective in improving the knowledge and skills of final year midwifery students.